A non-uniform birthday problem with applications to discrete logarithms - Galbraith, Steven D.; Holmes, Mark (Discrete Applied Mathematics, 2012)
We consider a generalisation of the birthday problem that arises in the analysis of algorithms for certain variants of the discrete logarithm problem in groups. More precisely, we consider sampling coloured balls and placing them in urns, such that the distribution of assigning balls to urns depends on the colour of the ball. We determine the expected number of trials until two balls of different colours are placed in the same urn. As an aside we present an amusing “paradox” about birthdays.